Improving The Organizational Citizenship Behaviour (Ocb) Through Developing Job Satisfaction And Interpersonal Communication (Empirical Study At Junior High-Schools In Bogor, Indonesia) - Suchyadi, Yudhie; Soiman, Agus (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
The teachers’ Organizational Citizenship Behaviour (OCB) becomes an important factor in the teaching process at school. Unfortunately, based on the preliminary survey at several Junior High-School in Bogor, it had been found that many teachers had a low level of OCB. Also, it had been found that teachers had low levels of job satisfaction and ineffective interpersonal communication. Based on that issues, we formulated the objectives of this research to improve the teachers’ OCB through developing job satisfaction and interpersonal communication. The objectives of improving teachers’ OCB will become an effective effort to improve the teaching process in the classroom and further will improve the quality of education. This research was carried out on 266 teachers from 20 Junior High-Schools, in Bogor. This research used a quantitative method and used the correlational technique to assess the degree of relationship among those variables. The findings of this research can be summarized that there is a positive and significant correlation: between job satisfaction with OCB (r = 0.605, p0.01), between interpersonal communication with OCB (r = 0.604, p0.01)and between job satisfaction and interpersonal communication simultaneously with OCB (r = 0.613, p0.01). Based on those findings, it can be concluded that job satisfaction, as well as interpersonal communication, have the strength to predict teachers’ OCB. These findings supported the recommendations to improve OCB by developing teachers’ job satisfaction and interpersonal communication.Organizational Citizenship Behaviour (OCB), Job Satisfaction, and Interpersonal Communication